Metagenomic Sequencing Reveals that High-Grain Feeding Alters the Composition and Metabolism of Cecal Microbiota and Induces Cecal Mucosal Injury in Sheep - Fei Xie (American Society for Microbiology, 2021)
High-grain (HG) diets are known to alter the rumen microbiome. However, the responses of the hindgut microbiota and its epithelial function need further investigation in ruminants.